Personal BioBlitz: A New Way to Encourage Biodiversity Discovery and Knowledge in K–99 Education and Outreach. (14th October 2015) - Pollock, Nicholas B.; Howe, Natalie; Irizarry, Ivelisse; Lorusso, Nicholas; Kruger, Ariel; Himmler, Kurtis; Struwe, Lena
Abstract: Broad and detailed knowledge about common species in everyday life has decreased among the public. Even biology researchers may be largely unaware of our everyday biodiversity. To counter such "species blindness" and create long-term excitement and learning about the biodiversity we see every day, we arranged 76-day BioBlitzes at Rutgers University (New Jersey, United States) in 2014 and 2015, in which participants identified and listed all species they discovered. The result was 7270/11748 observations from 30/78 participants and 7/13 countries, including 3458/3057 unique taxa, 91%/99.9% identified to the species level, and 80%/54% listed only by one person (2014/2015). Observations of organismal groups did not strongly correspond to the number of estimated species worldwide but appeared to be related to perceived charisma, body size, and organism mobility. Participants reported an increased ability to "see" species and to identify new groups, their learning of new tools of species identification, and a strong increase in their biodiversity knowledge and eagerness to learn more.